Effect of heat input on a laser powder deposited Al/steel butt joint. (April 2019) - Xia, Hongbo; Zhang, Liankai; Tan, Caiwang; Wu, Laijun; Chen, Bo; Li, Liqun
Highlights: Al/steel butted joints were successfully joined by laser powder deposition. Interfacial IMC evolution and thermal cycles were observed and evaluated. Joint with highest tensile strength of 193.6 MPa was produced. Abstract: Joining dissimilar metals, such as Al to steel, in butt configuration was successfully realized by laser powder deposition. Satisfactory weld appearances were produced when the laser powers were 1800 W and 2200 W. No obvious interfacial reaction layer was generated when the laser power was 1200 W, and only τ5 -Fe1.8 Al7.2 Si phase (1–3 μm) was produced when the laser power was 1500 W. A 3-μm-thick τ5 -Fe1.8 Al7.2 Si phase, 5-μm-thick mixed intermetallic compound (IMC) (θ-Fe(Al, Si)3  + τ5 -Fe1.8 Al7.2 Si phases) and 1-μm-thick τ5 -Fe1.8 Al7.2 Si phase were produced, respectively, at the top, middle and bottom regions when the laser power became 1800 W. Additionally, 8-μm-thick and 10-μm-thick mixed IMC (η-Fe2 (Al, Si)5  + θ-Fe(Al, Si)3  + τ5 -Fe1.8 Al7.2 Si) phases were produced, respectively, in the top and middle regions while only a 5-μm-thick θ-Fe(Al, Si)3  + τ5 -Fe1.8 Al7.2 Si phase was produced in the bottom region when the laser power increased to 2200 W. Numerical results showed that the highest peak temperature in the middle region led to the thickest IMC in this region. Highest tensile strength (194 MPa) and largest fracture displacement (0.35 mm) were both obtained in the joint produced when the laser power was 1800 W. Poor weld formation, a lack of an IMC layer at the interface and a newly formed η-Fe2 (Al, Si)5 phase were all harmful for the tensile properties of the joint.